Emerging Socialities in 21st Century Healthcare - Hardon, Anita; Hadolt, Bernhard; Project Muse; Project Muse. (Project Muse, 2017)
The landscape of healthcare is changing rapidly, both on an organisational and a technological level. This book gathers medical anthropologists to examine the ways that both patients and health care workers are being affected by new policies, market, and technologies. Contributors cover a wide range of topics, including vaccination, disability, migration, and self-medication, making clear that not only are changing circumstances leading to the emergence of new socialities, but they are also driving new ethics and moralities.
Based on contributions presented at the 7th Biannual Conference of the Medical Anthropology at Home (MAAH) network held in 2012 in Driebergen, The Netherlands.
Issued as part of book collections on Project MUSE.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Medical care -- Case studies; Medical ethics -- Congresses; Medical innovations -- Congresses; Medical anthropology -- Congresses; Social medicine -- Congresses; Electronic books; Case studies; Conference papers and proceedings; Electronic books